Guía para la implementación de la metodología BIM en empresas de Arquitectura - Oberto Vegas, Diana Valentina (Universidad Antonio Nariño, 2023)
This research will provide and offer the necessary instruments for a correct BIM implementation in a case study of an architecture company in Bucaramanga, Colombia in a simple, effective, and low-budget way. Therefore, this research, it is sought to demonstrate that an application guide for the implementation of the BIM methodology benefits architecture companies that aim to be more competitive with other companies, reduce time and costs in a project, as well as continuous improvement of its processes and implementation of new techniques.